Modernization of Ecology for Handling Abrasion in Riau Province - Fajriani Ananda (Syntax Corporation Indonesia, 2022)
Abrasion on the coast of Riau Province is becoming a serious problem that has not found an effective solution. The development of breakwaters and mangrove rehabilitation has not provided maximum benefits for the environment and society. The research was conducted in Mekong Village, West Tebingtinggi District, Meranti Islands Regency. The purpose of the study looked at how the model handled abrasion in the study area. Using a qualitative approach conducted interviews with the public, stakeholders and experts in the field of environment. Our results found there is a paradigm of handling abrasion that is wrong by making walls using both organic and plastic waste. This method has not shown effective results in withstanding ocean waves and preventing abrasion. However, in terms of environmental models handling abrasion with garbage deposits actually pollute the environment. To handle abrasion well we argue more modern ways are needed or apply the concept of ecological modernization. The concept integrates modern science and technology from industrial societies to repair damaged or threatened environments. Ecological modernization as well as being a sustainable development effort in the field of environment, especially coastal. The application of ecological modernization is challenged including the orientation of thinking that has not been in favor of modern concepts, softfkill limitations, capital, and stakeholder support. This portrait shows the need for stakeholder intervention and cohesiveness in supporting and implementing ecological modernization in handling abrasion to be more effective and efficient